Mobile Monitoring of Air Pollution Reveals Spatial and Temporal Variation in an Urban Landscape - Cummings, Lucas E.; Stewart, Justin D.; Reist, Radley; Shakya, Kabindra M.; Kremer, Peleg (Frontiers in Built Environment, 2021)
Urban air pollution poses a major threat to human health. Understanding where and when urban air pollutant concentrations peak is essential for effective air quality management and sustainable urban development. To this end, we implement a mobile monitoring methodology to determine the spatiotemporal distribution of particulate matter (PM) and black carbon (BC) throughout Philadelphia, Pennsylvania and use hot spot analysis and heatmaps to determine times and locations where pollutant concentrations are highest. Over the course of 12 days between June 27 and July 29, 2019, we measured air pollution concentrations continuously across two 150-mile (241.4 km) long routes. Average daily mean concentrations were 11.55 ± 5.34 µg/m3 (PM1), 13.48 ± 5.59 µg/m3 (PM2.5), 16.13 ± 5.80 µg/m3 (PM10), and 1.56 ± 0.39 µgC/m3 (BC). We find that finer PM size fractions (PM2.5) constitute approximately 84% of PM10 and that BC comprises 11.6% of observed PM2.5. Air pollution hotspots across three size fractions of PM (PM1, PM2.5, and PM10) and BC had similar distributions throughout Philadelphia, but were most prevalent in the North Delaware, River Wards, and North planning districts. A plurality of detected hotspots found throughout the data collection period (30.19%) occurred between the hours of 8:00 AM – 9:00 AM.